Conceptual Framework for Developing Web-based Maintenance Systems for Government’s Simple-Buildings within the DKI Jakarta Provincial Government - Pangastuti, Dyah Ayu; Latief, Yusuf (Journal of International Conference Proceedings, 2021)
DKI Jakarta, as the capital of the Republic of Indonesia, has the highest population density in Indonesia, with a population of 16,334 people / km2. Therefore, community facilities and infrastructure within the DKI Jakarta Provincial Government play an important role so that community service can be carried out properly. As one of the main infrastructures, State Buildings must have building reliability as stated in the technical requirements stipulated in Presidential Regulation Number 73 of 2016. Building maintenance is an activity to maintain the building's reliability and infrastructure, and facilities so that the building always functions properly. Based on a survey conducted by the DKI Jakarta Provincial Office for The Creation of Works, Spatial Planning and Land Use in 2019, the number of building assets of Province DKI Jakarta are 9823 buildings. 60% of those buildings were classified as Simple-Building category. Due to the numerous building assets, maintenance activities need to be supported by an adequate maintenance system. This study aims to develop a building maintenance system based on web. The methodology used in this research are expert validation, interviews, field survey and literature studies. The results of the validation process will be developed into a simple-building’s web-based maintenance system framework.